New approaches to the study of tourist experiences in time and space. Issue 1 (1st January 2016) - Birenboim, Amit
ABSTRACT: Nowadays, a growing number of researchers are investigating subjective attitudes of people toward their environment with ever-increasing spatial and temporal resolutions. It seems that researchers' interest in daily experiences is not merely a passing research fad, but rather that individuals in current societies find more interest in their own momentary experiences. They talk about their affective states, they spend considerable portions of their income on intangible experiences, and they instantly share personal 'moments' through various online social media platforms. These trends are even more apparent in the tourism and leisure industries which aim to generate positive experiences among individuals. This research note points out new directions in the exploration of experiences during tourism and leisure activities. It discusses a new relevant concept, subjective momentary experiences on one hand and presents novel methodological opportunities on the other. In order to portray these new trends, a case study that describes the episodic experiences of festival attendants in a high tempo-spatial resolution is presented.